The Effectiveness of Augmented Reality-Based Sispen Media in Improving the Understanding of The Digestive System Concept of Elementary School Students - Silvyra Rismawati; Aji Septiaji; Devi Afriyuni Yonanda (Eduvest - Journal of Universal Studies, 2026)
This study aimed to examine the effectiveness of SISPEN (Digestive System) learning media based on Augmented Reality (AR) in improving elementary school students’ conceptual understanding of the human digestive system. The increasing demand for innovative digital learning media in the 21st century, particularly for abstract science topics, underscores the urgency of developing interactive and immersive learning tools. This research employed a quantitative approach using a pre-experimental design with a one-group pretest–posttest design. A total of 24 fifth-grade students aged 10–11 years from SDN Majalengka Wetan VII participated in this study and were selected using purposive sampling. Data were collected through conceptual understanding tests (pretest and posttest), student motivation questionnaires, and classroom observation sheets. The results showed a significant increase in students’ average scores from 52.33 (pretest) to 77.62 (posttest). The N-gain value of 0.54 indicated a moderate level of effectiveness, with 63% of students categorized in the moderate gain category and 21% in the high gain category. The paired-sample t-test confirmed a statistically significant difference between pretest and posttest scores (t = 38.77, p < 0.05). In addition, students demonstrated a very positive response toward the AR-based media, with an average motivation score of 3.49 (very good category). These findings suggest that SISPEN AR-based learning media effectively enhances both cognitive understanding and learning motivation among elementary school students. This study contributes to the development of AR-based digital learning media aligned with constructivist pedagogy and the TPACK framework in Indonesian primary education contexts.